2009
DOI: 10.1200/jco.2008.19.6550
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Decitabine Administered Daily for 5 Days Every 4 Weeks to Adults With Myelodysplastic Syndromes: The Alternative Dosing for Outpatient Treatment (ADOPT) Trial

Abstract: Purpose Decitabine, a DNA-targeted hypomethylating agent, is approved by the United States Food and Drug Administration for treatment of patients with myelodysplastic syndromes (MDS) on a schedule of 15 mg/m2 administered via intravenous (IV) infusion every 8 hours for 3 days. This study assessed the efficacy and safety of an alternative dosing regimen administered on an outpatient basis in academic and community-based practices. Patients and Methods Patients were treated with decitabine 20 mg/m2 by IV infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(222 citation statements)
references
References 13 publications
9
208
2
3
Order By: Relevance
“…More recently, Cashen et al reported results of a three-institution trial of single-agent decitabine, targeting a patient population similar to that in the present study (median age in both studies was 74 years) (29). For 55 AML patients of age ≥ 60 who were not candidates for intensive therapy, the investigators administered 5 d of decitabine treatment per cycle, an approach identical to that previously published for MDS (30,31). With the 5-d approach, the CR rate was 24% and the overall response rate 25%.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, Cashen et al reported results of a three-institution trial of single-agent decitabine, targeting a patient population similar to that in the present study (median age in both studies was 74 years) (29). For 55 AML patients of age ≥ 60 who were not candidates for intensive therapy, the investigators administered 5 d of decitabine treatment per cycle, an approach identical to that previously published for MDS (30,31). With the 5-d approach, the CR rate was 24% and the overall response rate 25%.…”
Section: Discussionmentioning
confidence: 81%
“…for 3 days every 6 weeks, potentially higher CR rates may be obtained by administering DEC at dose/schedule of 20 mg/m 2 /day i.v. for 5 days every 28 days in other trials, 6,9 as this is the dose and schedule we employed in the current study.…”
Section: Conditioning Regimenmentioning
confidence: 99%
“…3 Although DEC did not significantly extend OS, 4,5 the overall response rate to DEC among patients with highrisk MDS was 30-49%. [6][7][8][9] Lenalidomide has been reported to reduce anemia and transfusion dependence among MDS patients with a chromosome 5q deletion. 10 Although these agents have induced hematological and cytogenetic responses in a substantial portion of patients, these therapies are not curative.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MDS or secondary acute myeloblastic leukemia (sAML) respond very poorly to chemotherapy and in higher risk patients, survival is below 10% at 2 years. 7-9 New medications such as demethylating agents have shown some hematological and survival improvements, [10][11][12][13] but allogeneic hematopoietic stem cell transplantation (HSCT) remains indicated in high-risk patients aged o60 years. 14- 16 Unfortunately, only 40-50% of patients will have a suitable HLA-matched donor.…”
Section: Introductionmentioning
confidence: 99%